Rasio-Rasio Keuangan Sebagai Prediktor Return Saham Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Wirasedana, I Wayan Pradnyantha; Ery Setiawan, Putu (E-Jurnal Akuntansi, 2020)
Financial ratios have been used long ago to assess a company's financial performance and predict future performance, including stock returns. The study aims to determine the predictive ability of various financial ratios to stock returns. Statistical testing with SPSS was conducted on 97 manufacturing companies on the Stock Exchange during the period 2009-2016 or as many as 748 observational data. Testing is done by performing a simple regression of each ratio and multiple regression using the stepwise method to identify ratios that are able to predict stock returns. Simple regression test results on each ratio show that the greatest predictive ability is owned by Return on Assets followed by Assets Turnover, Return on Equity, Debt to Equity Ratio and Earnings per Share. Multiple regression testing using the stepwise method shows that the combination of the ratio of Return on Assets, Debt to Equity Ratio and Inventory Turnover provides the greatest predictive ability among the ratios tested.  Keywords: Debt To Equity Ratio; Financial Ratios; Return On Assets, Stock Returns; Turnover.